Streptokinase resistance: when might streptokinase administration be ineffective?. Issue 11 (November 1992) - Buchalter, Maurice B; Suntharalingam, Ganesh; Jennings, Ian; Hart, Catherine; Luddington, Roger J; Chakraverty, Ronjon; Jacobson, S Kim; Weissberg, Peter L; Baglin, Trevor P
Abstract : Objective —( a ) To develop an assay for streptokinase resistance. ( b ) To determine the prevalence of streptokinase resistance in patients presenting with acute myocardial infarction for the first time. ( c ) To determine the prevalence of streptokinase resistance in patients after exposure to streptokinase or streptococcal infection. Design —Open, prospective. Patients —30 healthy volunteers. 40 patients admitted to the coronary care unit at Addenbrooke's Hospital with suspected acute myocardial infarction, 12 patients 12 months after streptokinase treatment, eight patients 24 months after streptokinase treatment, and sera from 12 patients with raised antistreptolysin O (ASO) titres. Methods —Three assays were used; a dilution neutralisation assay, an enzyme linked immunosorbent assay (ELISA) for immunoglobulin G (IgG) antistreptokinase antibodies, and an in vitro fibrin plate lysis assay. All measurements were performed on venous blood samples. Results —Neutralisation and IgG antibody titres were positively correlated. Mean (SEM) antistreptokinase concentrations in the 30 controls were 87 (10) U/ml (neutralisation assay) and 28 (6·3) U/ml (ELISA). Corresponding concentrations in patients before streptokinase were 68 (6·1) U/ml and 18 (4·5) U/ml with a mean fibrin plate assay 117 (7·1)% that of controls. Resistance to streptokinase was detectable in one patient after 72 hours and in all patients by day 10. By day 10 concentrations were 4388 (919) U/ml, 773 (109) U/ml, and 17 (5·4)%. At both 12 and 24 months resistance was present in 75% of patients. Similarly 66% of high ASO titre sera showed resistance. The fibrin plate lysis assay detected significantly reduced streptokinase dependent fibrinolysis in vitro in the absence of raised total concentrations of antistreptokinase antibodies. Conclusions —The prevalence of streptokinase resistance in patients presenting with their first myocardial infarction is low. Resistance develops early after treatment and is still present in 75% of patients after 24 months. Retreatment with streptokinase is likely to be suboptimal even after 24 months. The fibrin plate lysis assay detects resistance in patients with normal concentrations of streptokinase antibodies. Streptococcal infection is associated with a high incidence of streptokinase resistance.